Inovasi Limbah Jagung Hibrida menjadi Briket Arang sebagai Upaya Peningkatan Literasi Ekonomi Masyarakat Kabupaten Enrekang Sulawesi Selatan - Ismaya, Ismaya; Galib, Andi Ahmad Chabir; Nurhapisah, Nurhapisah; Ridwan, Madinatul Munawwarah; Sitonda, Syawal (Jurnal Pengabdian UNDIKMA, 2024)
This community service program aims to enhance the knowledge and skills of the members of the Papaling Women's Farmers Group (KWT.PAPALING) in processing hybrid corn waste into charcoal briquettes (bricorn) as an effort to improve the community's economic literacy. The implementation methods for this service include situational and problem analysis, economic literacy workshops, charcoal briquette (bricorn) production training, charcoal briquette (bricorn) marketing training, followed by an evaluation phase. The evaluation instruments used in this activity are questionnaires, which are analyzed descriptively. The activity is carried out in Bamba Puang Village, Anggeraja District, Enrekang Regency, South Sulawesi Province. The result of this community service activity is the increased knowledge and skills of KWT.PAPALING members in processing hybrid corn waste into charcoal briquettes. Additionally, the community has learned how to calculate production costs, set competitive selling prices, and implement effective marketing strategies. With this enhanced knowledge and skills, the community is expected to independently manage the production of bricorn, thereby increasing family income and improving local economic well-being.